Teacher Presence: what is it and how can we achieve it? - Turdaliyeva Mohlaroyim Mahammadismoil qizi (Genius Journals, 2022)
The article gives data about what teacher presence is and how can we – as we are preservice teachers – acquire it so that we can deliver our speech with our confidence by strongly claiming our presence in a classroom. Moreover, it goes into in-depth details about the mistakes non-professional teachers make and presents tips so as to avoid them.
Keywords: Teacher presence; good presence; bad presence; body language